Silica layers produced by the sol-gel method as dielectric masks in ion exchange processes - Rogoziński, Roman; Karasiński, Paweł; Tyszkiewicz, Cuma (Photonics Letters of Poland, 2012)
<!-- saved from url=(0022)http://internet.e-mail --> This paper presents experimental results of produced by the sol-gel method silica layers usage as dielectric masks in ion exchange processes in producing stripe waveguides. Such layers were produced on the glass substrate (soda-lime glass) by the dip-coating method. Their thicknesses gained during single deposit on the substrate were in the range of 78÷150nm. Those layers had compactness comparable to the thermal silica. The Ag+↔Na+ ion exchange processes with the use of AgNO3/NaNO3 solution with the mole fraction of κAg=0.0025 were completed. The permeability of the layers for dopant ions (Ag+) depending on the thickness of the layer and the diffusion time was tested. Full Text: PDF References E. Okuda, I. Tanaka, T. Yamasaki, "Planar gradient-index glass waveguide and its applications to a 4-port branched circuit and star coupler", Appl. Opt. 23, 1745 (1984). CrossRef S.I. Najafi, "Optical behavior of potassium ion-exchanged glass waveguides", Appl. Opt. 27, 3728 (1988). CrossRef J.G. Gallagher, R.M. De la Rue, "Single-mode stripe optical waveguides formed by silver ion exchange", Electr. Lett. 12, 397 (1976). CrossRef P. Simova, J. Savatinova, T. Tsonev, "Propagation characteristics of Ag+ ion-exchanged stripe waveguides", Appl. Phys. 22, 237 (1980). CrossRef P. Karasiński, "Influence of technological parameters on the properties of sol-gel silica films", Opt. Applicata, 35, 117 (2005). DirectLink P. Karasiński, R. Rogoziński, "Rib waveguides fabricated by means of chemical etching of sol–gel SiO2:TiO2 films", Opt. Comm. 245, 237 (2005). CrossRef P. Karasiński, C. Tyszkiewicz, R. Rogoziński, J. Jaglarz, J. Mazur, "Optical rib waveguides based on sol-gel derived silica–titania films", Thin Solid Films 519, 5544 (2011). CrossRef R. Rogozinski (2012). Ion Exchange in Glass – The Changes of Glass Refraction, Ion Exchange Technologies, Ayben Kilislioglu (Ed.), ISBN InTech. DirectLink J.M. White, P.F. Heidrich, "Optical waveguide refractive index profiles determined from measurement of mode indices: a simple analysis", Appl. Opt. 15, 151 (1976). CrossRef